DESIGN OF UNMANNED AIR SYSTEMS FOR USE IN SEARCH AND RESCUE IN THE NORTH ATLANTIC - Melin, Tomas (Fluida och mekatroniska system, 2012)
A comparison of aircraft performance and program costs involved with unmanned air vehicle (UAV) projects has been performed. The assessment has been taken from a systems engineering point of view when designing a new unmanned air system for a search and rescue case study. Two different design strategies were investigated, one being a traditional aircraft system with servicing and maintenance intervals and the other being a single use aircraft system. The design paradigm is design-to-objective, whilst optimizing for cost.The primary objective is to assess the size of a search and rescue scenario to determine when a single use expendable system becomes more cost effective than a traditional reusable design. To be able to holistically assess the operational effectiveness of the search and rescue system, aircraft subsystems and the system level need to be modeled.